2005
DOI: 10.4102/sajip.v31i1.179
|View full text |Cite
|
Sign up to set email alerts
|

Occupational stress, organisational commitment and ill-health of employees at a higher education institution in South Africa

Abstract: The objectives of this study were to assess the indicators and moderators of occupational stress at a higher education institution in South Africa, as well as differences based on language and years of experience at the institution. A cross-sectional survey design was used. The participants included academic and support staff at a higher education institution (N = 372). An Organisational Stress Screening Tool (ASSET) and a biographical questionnaire were administered. Workload, control, work-relationships and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
31
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 35 publications
4
31
0
Order By: Relevance
“…Barkhuizen and Rothmann [17] found in their study among tertiary institutions in South Africa, that academics are experiencing high levels of academic stress related to remuneration, fringe benefits, work overload and work-life balance. These results are similar to those of Coetzee and Rothmann [18] who reported that work overload is a major source of stress for higher education staff in South Africa. The latter which leads to low morale is one of the burning issues in the current South African government and all these factors will be investigated in hypothesis 1.…”
Section: Literature Reviewsupporting
confidence: 81%
“…Barkhuizen and Rothmann [17] found in their study among tertiary institutions in South Africa, that academics are experiencing high levels of academic stress related to remuneration, fringe benefits, work overload and work-life balance. These results are similar to those of Coetzee and Rothmann [18] who reported that work overload is a major source of stress for higher education staff in South Africa. The latter which leads to low morale is one of the burning issues in the current South African government and all these factors will be investigated in hypothesis 1.…”
Section: Literature Reviewsupporting
confidence: 81%
“…Catano et al, 2010;Coetzee & Rothmann, 2005;Kinman, Jones & Kinman, 2006;Tytherleigh, Webb, Cooper, & Ricketts, 2005;Winefield, Boyd, Saebel, & Pignata, 2008). Research that has tracked the work-related wellbeing of academics working in the United Kingdom (UK) over several years (from 2008 to 2014) suggests that the demands experienced by academics have increased over time and the resources that have traditionally protected them from work-related stress, such as autonomy, support and role clarity, have eroded (Kinman & Wray, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Meyer and Allen (1997) also suggested that the organisation's support of academics explained their emotional commitment towards their universities. Interestingly, Coetzee and Rothmann (2005) found that while university staff members were committed to their institutions, they perceived a lack of commitment from their employer. In addition, Millward-Brown (1996) found that university and college lecturers reported lower levels of perceived commitment from their organisation when they were compared with 20 other occupational groups.…”
mentioning
confidence: 99%
“…In a study by Winefield et al (2002), the majority of the respondents reported experiencing tiredness 'sometimes' to 'nearly all the time', back and neck pains, sleeping difficulties, headaches, muscle pain, colds and virus infections. Furthermore, in the South African context, Coetzee and Rothmann (2005) recently found high levels of psychological and physical ill health in a sample of 372 university staff members.…”
mentioning
confidence: 99%